Index, McIntosh County, E - (:unkn) unknown (United States Government)
Oklahoma aerial photographs in this collection are public domain and were created by U.S. government agencies or contractors to those agencies. The photos are marked with a flight and frame number at the top of the photos, e.g., AQS-219. The date of the flight is then printed in the opposite corner. More information about these photos can be found at: http://guides.ou.edu/aerial. Digital imaging courtesy of the University of Oklahoma Libraries, Government Documents Collection.
Black and white photography of McIntosh County, OK, USA